Global burden of type 2 diabetes in adolescents from 1990 to 2019 - Luo, Juan; Hou, Jiahui; Yi, Jinglin; Li, Langbo; Zhao, Xinlan (Frontiers in Endocrinology, 2024)
Purpose: To evaluate the burden of type 2 diabetes (T2D) among adolescents (15-24 years old) from 1990 to 2019.The age-standardized incidence rate (ASIR) and disability-adjusted life years (DALYs) rate of adolescents were analyzed according to age, sex, geographical location, and sociodemographic index (SDI). The estimated annual percentage change (EAPC) was estimated to quantify the trends.From 1990 to 2019, the ASIR (EAPC = 1.07) and age-standardized DALY rate (EAPC = 2.01) of T2D in adolescents showed an increasing trend. The ASIR was higher in males than in females. The burden was greater in the 20-24-year age group. Of the five SDI regions, the highest ASIR and age-standardized DALY rate were found in low-middle-SDI regions, while the greatest increase in these rates was observed in high-SDI regions (EAPC = 3.28 and 3.55, respectively). Of the 21 regions analyzed, the highest ASIR and age-standardized DALY rate were found in Oceania. Of the 204 countries analyzed, the Marshall Islands (651.16) and Kiribati (277.42) had the highest ASIR and DALYs, respectively. The regions with the greatest increase in the ASIR from 1990 to 2019 were Western Europe (EAPC = 4.15), high-income North America (EAPC = 4.72).The global burden of T2D in adolescents showed an overall upward trend from 1990 to 2019. It is necessary to strengthen prevention measures related to risk factors for T2D among young people, especially in areas with a low-to-medium SDI.